A Systems study on the Parts Distribution Department of Monark Equipment Corporation - Del Castillo, Ma. Isabel (College of Engineering, 1989)
As was specifically requested by the management of the Monark management, a manual for the systems and procedures (S& P) of Parts Distribution Department (PDD) was designed (See Volume 2). The manual consists of a straight-forward documentation of existing S&P followed by recommendations on how to improve it. As for the forms in PDD, for example, the eventual elimination of the picking note is recommended upon accomplishment of a 98% binning accuracy (estimated by Traffic and Warehouse Manager to be achieved by middle of 1989). However, while this is still being worked at, eliminations of certain copies of computer-generated forms can be started. The forms applicable in this case are: Sales, Shop and Proforma Invoices, Order Confirmed Form, Credit Notes, Quotation Form, Parts Sales Backorder Form, and Parts Order reprint. The proposed forms flow and printer set-up are also shown in the manual. Designed for its intended use as a reference, the main procedures of the PDD sections (Counter Sales, Order, Analysis and Indent Order) are charted in detail. From these, procedures incorporating the form analysis recommendations and certain procedural changes are recommended. Changes in procedures include: elimination of picking note-related operations, installation of an archive especially for computer-generated forms, color-coding for leadtime-related procedure charts, and the development of a software program for Analysis Section reports. The last procedural change proposed for PDD is envisioned to simplify report preparation of Statistical Inventory Analyst so that more time can be spent on analysis of the output and evaluation of information analyzed. Due to the importance of the evaluation of information, the responsibility of maintaining the archive can be assigned to the analyst. This task, of course, can be delegated to others depending of the outcome of the Work Distribution Study that is aimed to check the load of the PDD personnel. The study can be conducted by the Personnel Department upon request of the PDD Manager. In any system, one mechanism to assure conformity to the standard procedures is strict supervision. This can be more objectively done, however, if realistic time standards are present. Whether the standards are derived from present or proposed system of PDD, the time study can still be conducted based on the procedural detail of the procedure charts. Such a function was actually considered in the charting. In the area of inventory control, an alternative forecasting system is presented by our group. Recommendations as to activities that must characterize the system cover: parts that need immediate supervision, determination of the most appropriate forecasting method, classification of parts under regular stock orders, and the consequent elimination of stocks. As for the PDD's inability to meet the shop's demand as effectively as it meets Counter Sale's, a collective forecasting system can be employed. Here, the Service Department in conjunction with the Sales Department is expected to submit job forecasts to the Analysis Section for proper conversion to parts forecast. This can provide a more concrete basis in meeting shop orders than the present forecasting method applied. Lastly, one more recommendation for immediate implementation (aside from the time study) is the consideration of ergonomic factors in planned layout of the company. This will provide the conducive working environment so important in any undertaking.